1988
DOI: 10.1037/0022-3514.54.4.605
|View full text |Cite
|
Sign up to set email alerts
|

Impact of employee mobility and employee performance on the allocation of rewards under conditions of constraint.

Abstract: We advanced and tested a multiple-motive model of resource allocation. In this model we identified important instrumental, social-emotional, and group maintenance goals, and asserted that rational managers will sometimes allocate reduced rewards to employees with constrained mobility. Consistent with predictions, managers allocated greater salary funds to more deserving employees: those with high competence and dedication. However, allocations also differed as a function of employee mobility. This effect was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…The results also offered some support for multiple-motive theories (Farkas & Anderson, 1979;Greenberg & Cohen, 1982;Leventhal, 1976;Rusbult, Lowery, Hubbard, Maravankin, & Neises, 1988). Many subjects, mostly older, gave several discernible explanations for their allocations to the younger and poorer student involving a combination of need, effort, and sympathy, suggesting that older children are guided by several motives simultaneously, at least in multi-attribute situations.…”
Section: Discussionsupporting
confidence: 50%
“…The results also offered some support for multiple-motive theories (Farkas & Anderson, 1979;Greenberg & Cohen, 1982;Leventhal, 1976;Rusbult, Lowery, Hubbard, Maravankin, & Neises, 1988). Many subjects, mostly older, gave several discernible explanations for their allocations to the younger and poorer student involving a combination of need, effort, and sympathy, suggesting that older children are guided by several motives simultaneously, at least in multi-attribute situations.…”
Section: Discussionsupporting
confidence: 50%
“…For example, when limited upward mobility makes it unlikely that lower paid people can ever earn substantially greater financial rewards, they appear to find solace in more equally distributed socioemotional rewards, such as interpersonal warmth (Greenberg and Ornstein, 1983;Kanter, 1977;Martin et al, 1983). Research by Rusbult et al (1988Rusbult et al ( , 1990 has shown that allocators practice rational selective exploitation, distributing lower salaries to individuals with constrained mobility. If future research could show that lower income people find counterbalanced reward systems more just, if they willingly accept roses in lieu of more bread, this would contribute to our understanding of why, in the United States, financial inequality is so often considered just, even by those who receive relatively little (e.g., Crosby, 1982;Lane, 1962;Martin, 1986b;Stouffer et al, 1949).…”
Section: Discussionmentioning
confidence: 95%
“…Rusbult and her colleagues (Rusbult, Lowery, Hubbard, Maravankin, and Neises, 1988) argue that allocation decisions stemming from the combination of these goals depend also on the mobility of the employees and availability of both labor and rewards. Rusbult and her colleagues (Rusbult, Lowery, Hubbard, Maravankin, and Neises, 1988) argue that allocation decisions stemming from the combination of these goals depend also on the mobility of the employees and availability of both labor and rewards.…”
Section: Goals and Motivations: In Pursuit Of Distributive Justicementioning
confidence: 99%